Swept away - O'Leary, Beth (Berkley Romance, 2025)
"Two strangers find themselves in a tricky situation when one night turns into days of being stranded at sea in this epic new love story by bestselling author Beth O'Leary. What if you were lost at sea...with your one-night stand? Zeke and Lexi thought it would just be a night of fun. They had no intentions of seeing each other again. Zeke is only in town for the weekend to buy back his late father's houseboat. Lexi has no time for dating when she needs to help take care of her best friend's daughter. Going back home with a stranger seems like a perfect escape from their problems. But a miscommunication in the dark, foggy night means no one tied the houseboat to the dock. The next morning, Zeke and Lexi realize all they can see is miles and miles of water. With just a few provisions on the idle boat, Zeke and Lexi must figure out how to get back home. But aside from their survival, they're facing another challenge. Because when you're stuck together for days on end, it gives you a lot of time to get to know someone-and to fall in love with them"--